Resistance circuit training and psychology increasing archery accuracy - Yudho, P. K.; Kusnanik, N. W.; Wiriawan, O.; Hartono, M.; Sumartiningsih, S. (Fizjoterapia polska: Polish Journal of Physiotherapy, 2025)
Aim of the study. The purpose of this study was to analyze the effect of resistance circuit training and psychological techniques on archery accuracy at distances of 50, 40, and 30 meters. This research was conducted as a quasi-experimental study using a matching-only design. Subjects were divided into two groups: (K1) athletes trained with mental imagery and circuit training using equipment, and (K2) athletes trained with mental imagery and circuit training without equipment. The intervention lasted for six weeks, with training sessions three times per week.